2013
DOI: 10.1080/19317611.2012.728554
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Influencing Male Condom use Among University Students in Portugal

Abstract: A self-administered questionnaire was carried out among university students in Portugal, with the aim to examine determinants influencing male condom use, according to the information-motivation-behavioral skills model (J. Fisher & Fisher, 1992). Students' levels of information, motivation, and behavioral skills regarding preventive sexual behavior (male condom use) were ascertained and were used to determine their association with condom use among 880 male and 1,807 female students aged 18 to 35 years old. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
2
10
1
9
Order By: Relevance
“…Attitude is an important construct that affects health behaviours, Reis et al. () observed that university students with more positive attitudes tended not to accept sexual risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitude is an important construct that affects health behaviours, Reis et al. () observed that university students with more positive attitudes tended not to accept sexual risks.…”
Section: Discussionmentioning
confidence: 99%
“…Biases in judgement such as excessive optimism, increased confidence and psychological distancing might explain why knowledge does not predict the perception of risk (Adefuye et al 2009;Kabwama & Berg-Beckhoff 2015). Attitude is an important construct that affects health behaviours, Reis et al (2013) observed that university students with more positive attitudes tended not to accept sexual risks.…”
Section: Cognitive and Psychosocial Factors Associated With Risk Behamentioning
confidence: 99%
“…Em relação ao comportamento de utilização do preservativo, as médias encontradas são semelhantes às de estudos desenvolvidos com amostras portuguesas (Gomes & Nunes, 2011b;Muñoz-Silva, Sánchez-García, Martins, & Nunes, 2009, Reis, Ramiro, Matos, & Diniz, 2013. É ainda de notar que a média de utilização do preservativo na amostra revela-se inconsistente, apesar de uma elevada intenção de uso.…”
Section: Discussionunclassified
“…Desta forma, é plausível compreender-se, porque apesar do conhecimento da existência e transmissão de infeções sexuais (por exemplo, Reis et al, 2013), o risco pessoal é geralmente percecionado como sendo inferior ao real, facto presente tanto em amostras portuguesas (Amaro et al, 2004), como em amostras não portuguesas (Adefuye, Abiona, Balogun, & Lukobo-Durrell, 2009;Kayiki & Forste, 2012). Deve-se, igualmente, considerar que a representação social integra informação no seu sistema periférico, sem no entanto modifi car os valores e crenças centrais.…”
Section: Discussionunclassified
“…supported by data collected from highly diverse populations that are of considerable relevance to the HIV epidemic, including, for example, men who have sex with men (MSM) (Fisher et al, 1994), adolescents (Fisher et al, 1999;Kalichman, Stein, et al, 2002;Robertson et al, 2006;Ybarra et al, 2013), university students (Bazargan et al, 2000(Bazargan et al, , 2010Fisher et al, 1994;Reis et al, 2013), low-income urban women , IDUs (Bryan et al, 2000), patients attending sexually transmitted infection (STI) clinics (Crosby et al, 2008;Kalichman et al, 2006;Mittal et al, 2012;Scott-Sheldon et al, 2010;Walsh et al, 2011), individuals with mental illness (Kalichman, Malow, et al, 2005), female commercial sex workers (Zhang et al, 2011), truck drivers (Bryan et al, 2001), and people living with HIV/AIDS (PLWH) . The propositions of the IMB model have received consistent empirical support in culturally and geographically diverse locations including Angola, Portugal, Malawi, and India, and multiple culturally and ethnically distinct settings in South Africa and the United States.…”
Section: Empirical Support For the Imb Model Of Hiv/aids Preventive Bmentioning
confidence: 99%